2014
DOI: 10.1155/2014/759642
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Aged Garlic Extract on Nonsteroidal Anti‐Inflammatory Drug‐Induced Gastric Inflammations in Male Albino Rats

Abstract: Natural products have long gained wide acceptance among the public and scientific community in the gastrointestinal ulcerative field. The present study explore the potential effects of aged garlic extract (AGE) on indomethacin-(IN-) induced gastric inflammation in male rats. Animals were divided into six groups (n = 8) control group, IN-induced gastric inflammation group via oral single dose (30 mg/kg to fasted rats) two AGE orally administered groups (100 and 200 mg/kg for 30 consecutive days) two AGE orally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…SOD plays an important role in preventing gastric ulcer by catalyzing the breakdown of highly reactive radical superoxide (O 2-) into oxygen and hydrogen peroxide [79,80]. In agreement with the report of [81,15] the inhibition of the antioxidant enzymes, SOD and GST following SGU in the present study may be due to the enhancement of the lipid peroxidation which, inhibit protein synthesis and consequently the activities of certain enzymes. In contrary, IND and cold stress induced a significant increase in the CAT activity in the gastric and duodenal tissues.…”
Section: Discussionsupporting
confidence: 91%
“…SOD plays an important role in preventing gastric ulcer by catalyzing the breakdown of highly reactive radical superoxide (O 2-) into oxygen and hydrogen peroxide [79,80]. In agreement with the report of [81,15] the inhibition of the antioxidant enzymes, SOD and GST following SGU in the present study may be due to the enhancement of the lipid peroxidation which, inhibit protein synthesis and consequently the activities of certain enzymes. In contrary, IND and cold stress induced a significant increase in the CAT activity in the gastric and duodenal tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has shown the immunotherapeutic potential of whole garlic extract, including its antiinflammatory, anticancer, and anti‐angiogenic effects. It has been shown to improve hyperglycemia and dyslipidemia, cardiovascular diseases, infectious diseases, autoimmune diseases, and allergies in various physiological tissues (Badr and Al‐Mulhim, ; Yin et al ., ; G et al ., ; Chandrashekar and Venkatesh, ). It is known that aqueous garlic extract is an antioxidant by scavenging reactive oxygen species and enhancing cellular antioxidant enzymes (superoxide dismutase, catalase, and glutathione peroxidase).…”
Section: Discussionmentioning
confidence: 99%
“…DADS effectively suppressed the production of proinfl ammatory mediators induced by ethanol and prevented the formation of gastric malondialdehyde and the depletion of reduced glutathione content and restored antioxidant enzyme activities, such as catalase, glutathione peroxidase and glutathione reductase in the gastric tissues of ethanol-treated rats. Aged garlic extract (AGE) especially at 200 mg/kg protected against indomethacin (IN)-induced gastric infl ammation in male rats as refl ected by signifi cant gastric mucosal healing of damage and reduction in the total microbial induced due to indomethacin administration (Badr and Al-Mulhim 2014 ). Further AGE normalised the signifi cant increase in malondialdehyde (MDA), myeloperoxidase (MPO), tumour necrosis factor-α (TNF-α) values and the signifi cant decrease in the total glutathione (tGSH), superoxide dismutase (SOD) and catalase (CAT) values induced by indomethacin.…”
Section: Gastroprotective Activitymentioning
confidence: 99%